Genes for laminarin degradation are dispersed in the genomes of particle-associated Maribacter species - Kalenborn, Saskia; Zühlke, Daniela; Reintjes, Greta; Riedel, Katharina; Amann, Rudolf I.; Harder, Jens (Frontiers in Microbiology, 2024)
Laminarin is a cytosolic storage polysaccharide of phytoplankton and macroalgae and accounts for over 10% of the world’s annually fixed carbon dioxide. Algal disruption, for example, by viral lysis releases laminarin. The soluble sugar is rapidly utilized by free-living planktonic bacteria, in which sugar transporters and the degrading enzymes are frequently encoded in polysaccharide utilization loci. The annotation of flavobacterial genomes failed to identify canonical laminarin utilization loci in several particle-associated bacteria, in particular in strains of Maribacter. In this study, we report in vivo utilization of laminarin by Maribacter forsetii accompanied by additional cell growth and proliferation. Laminarin utilization coincided with the induction of an extracellular endo-laminarinase, SusC/D outer membrane oligosaccharide transporters, and a periplasmic glycosyl hydrolase family 3 protein. An ABC transport system and sugar kinases were expressed. Endo-laminarinase activity was also observed in Maribacter sp. MAR_2009_72, Maribacter sp. Hel_I_7, and Maribacter dokdonensis MAR_2009_60. Maribacter dokdonensis MAR_2009_71 lacked the large endo-laminarinase gene in the genome and had no endo-laminarinase activity. In all genomes, genes of induced proteins were scattered across the genome rather than clustered in a laminarin utilization locus. These observations revealed that the Maribacter strains investigated in this study participate in laminarin utilization, but in contrast to many free-living bacteria, there is no co-localization of genes encoding the enzymatic machinery for laminarin utilization.